Optimising care and the patient experience for people living with dementia: The perceptions of radiography practitioners. (May 2023) - Higgins, R.; Spacey, A.; Innes, A.
Abstract: Introduction: Despite abundant literature on the diagnosis of dementia, limited research has explored the lived experiences by radiography practitioners when delivering care to people living with dementia (PLWD). This study explored the perceptions and compatibility of current professional guidance by both radiography practitioners and key stakeholders involved in developing the Society and College of Radiographers clinical practice guideline document for caring for people with dementia. Methods: This was a two-stage qualitative multi-method study. Fifteen diagnostic and two therapeutic radiography practitioners from across the UK participated with three asynchronous online discussion forums. One core member and three members from the key stakeholder group participated with individual semi-structured interviews. Data analysis included narrative and thematic analysis. Results: Participants from both stages identified enablers and barriers to providing person-centred care (PCC) to PLWD. Three superordinate themes were identified linked to (1) Challenges in delivering person-centred care to people living with dementia, (2) The need for role specific education and training, and (3) Partnership working with carers. Challenges in delivering care included time and resource pressures. The lack of dementia specific education compounded these difficulties. Care partners were seen as an asset to providing care. Conclusion: Providing PCC to meet the individual needs of PLWD can be challenging in practice. This is often due to time and resource implications. There were also issues with the identification of PLWD prior to their attendance in the department. Carers could help to alleviate some challenges. There is a need for profession specific education and dementia awareness training to support the provision of PCC to PLWD. Implications for practice: Dementia training needs to be specifically tailored for radiography practitioners to bridge the gap between guidelines and clinical practice rather than being generalised from other disciplines.